Analisis Kebutuhan Pembelajaran Siswa di SDN Sindangjaya IV - Magdalena, Ina; Ummah, Siti Azkiatul; Pratama, Rizki (Lembaga Yasin AlSys, 2023)
The purpose of this research is to find out the problems of students' difficulties with digital learning media in elementary schools. The purpose of this study is to find out what students want from digital teaching media. This study uses a descriptive qualitative approach. The purpose of choosing this approach is to determine whether or not digital teaching media is necessary for subjects. Several student representatives became research subjects. The lack of digital teaching media and the need for digital teaching media to support learning are problems that arise in the development of digital teaching media, according to the findings of research conducted in the field. Students can benefit from the availability of digital teaching materials, according to the researchers